Bias Gender dalam Teks Al-Qiraah Al-Rashidah (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2022)
Learning Arabic in Islamic boarding schools is always inseparable from the study of a text in Arabic to read, study, and understand the Arabic rules in it. Not just because it contains many lessons, this text study also contains many interesting new structures for language learning. Al-Qiraah al-Rashidah is a book taught in Islamic boarding schools that adopt the Gontor curriculum. This book is taught from grade two (2 Tsanawiyah) to grade five (2 Aliyah). As a book full of wisdom and new signs, this book should be free of values that contain gender bias. However, this imbalance between men and women occurs in one of the titles contained in this book, namely Kadzab al-Munajjimun wa Law Sadaqu. By drawing on the semiological theory, this paper concludes two things (1) the marker in this text is the full text of a story with the title Kadzab al-Munajjimun wa Law Sadaqu (2) the marker is interpreted as a woman who has no future to become a leader, famous, and respected. people. The women in the text are not entitled to get their rights in work and careers.